NO AGRARIAN REFORM: REVOLUTIE WITHOUT REVOLUTION? - Ganjar Razuni; Adilita Pramanti (University of Muhammadiyah Malang, 2020)
RI’s independence is a revolution to form a nation and state with an independentsocial structure. One of the instruments of de-colonization of the Indonesian peopleis the Agrarian Revolution. The matter of study in this paper is why, since Sokarnostepped down, the implementation of agrarian reform became half-hearted. Thiswriting method with a literature study through historical, descriptive analysis. Theresult reveals there has not been a fundamental change in the basic socio-agrarianstructure in Indonesia, and people fought for it from 2014 until now